Preparation method of MgB2 superconducting wire and MgB2 superconducting wire
By using electrochemical copper plating in MGB2 superconducting wire material to prepare CUFE composite tube and parcel Mgal alloy foil, the problem of coordinated deformation difference and MG stick plasticity of metal substrates is solved, and the deformation of the MGB2 superconducting wire is uniformly uniform Increases of sexual and load performance.
Patent Information
- Application Number
- CN202411942133.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-27
AI Technical Summary
In the preparation of existing MgB2 superconducting wires, the cold-bonded metal matrix has poor synergistic deformation and the central Mg rod have poor plasticity, resulting in uneven deformation of the wire core wire, uneven distribution of internal powder and poor density, affecting the structure of the superconducting wires. Integrity and current carrying performance.
The CuFe composite pipe is prepared by electrochemically plating copper on the surface of the Fe pipe, and the Mg powder rod is wrapped with MgAl alloy foil and inserted into the CuFe composite pipe. Through multi-pass rolling and cold drawing processing, combined with phase heat treatment, MgB2 is prepared Superconducting wire.
Through the close combination of CUFE composite tube and Mgal alloy foil, the deformation uniformity and internal denseness of the MGB2 superconducting wire material in the processing process are improved, and the load performance and critical current density of the wire are improved.
Smart Images

Figure CN119361230A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of superconducting wires, and in particular to a preparation method of a MgB2 superconducting wire and a MgB2 superconducting wire. Background Art
[0002] The critical transition temperature of practical MgB2 (magnesium diboride) superconducting wire is as high as 39K. It can be used in a refrigerator or liquid hydrogen (20K) environment, getting rid of the expensive liquid helium refrigeration cost. Therefore, it is considered to have great potential to replace low-temperature iron-titanium superconducting materials in the future MRI (Magnetic Resonance Imaging) market.
[0003] At present, the preparation of MgB2 wire is mainly based on powder tube filling. The precursor powder needs to be loaded into an outer sheath made of metal matrices such as Cu (copper), Nb (niobium), Fe (iron), and Monel (monel). After a series of rolling, rotary forging, and drawing processes, the phase heat treatment is performed to obtain the MgB2 superconducting wire. As a non-continuous macroscopic substance, the powder is mainly subjected to compressive stress from the outer sheath during the processing, and its deformation depends on the metal matrix. However, these outer sheaths are usually bonded together by cold bonding. Since there is no thermal process in the middle, the metal matrices are independent of each other and the metallurgical bonding effect cannot be achieved. The poor synergistic deformation between the metal matrices such as Cu, Nb, and Fe leads to uneven deformation of the wire core. In the multi-pass processing process, the internal powder distribution is inevitably uneven and the density is poor, which will seriously affect the integrity and current-carrying performance of the superconducting wire structure after phase formation. In recent years, the second-generation MgB2 superconducting wire using the central Mg diffusion method has become a research hotspot because it can obtain a higher critical current density. However, the central Mg rod used in this method has poor plasticity and is prone to breakage and necking during processing, which has become a limiting factor affecting its long wire preparation. Summary of the invention
[0004] The embodiments of the present application provide a method for preparing a MgB2 superconducting wire and a MgB2 superconducting wire, which are used to solve the problems of poor coordinated deformation of the cold-bonded metal matrix and poor plasticity of the central Mg rod in the prior art.
[0005] On the one hand, the present application embodiment provides a method for preparing a MgB2 superconducting wire, comprising: A Cu coating is attached to the outer surface of the Fe tube by electroplating to obtain a CuFe composite tube; Pressing Mg powder into Mg powder rods; Wrapping an MgAl alloy foil on the outer surface of a Mg powder rod, and inserting the Mg powder rod wrapped with the MgAl alloy foil into a CuFe composite tube; Fill B powder between the Mg powder rod and the CuFe composite tube, seal both ends of the CuFe composite tube, and obtain a MgB2 single core rod; The MgB2 single core rod is subjected to multiple rolling and cold drawing to obtain the MgB2 single core wire; The MgB2 single core wire is subjected to phase heat treatment to obtain the MgB2 superconducting wire.
[0006] On the other hand, an embodiment of the present application further provides a MgB2 superconducting wire, which is prepared by the above method.
[0007] The preparation method of a MgB2 superconducting wire and the MgB2 superconducting wire in the present application have the following advantages: 1. The copper-plated Fe tube surface was electrochemically plated to prepare a tightly bonded CuFe composite tube, which was then applied to the powder tube of the MgB2 single core rod. Compared with the conventional mechanical combination of Nb and Fe tubes in Cu tubes, the composite tube obtained by this method forms a strong coupling interface between Cu and Fe in an electrochemical manner, which can ensure that the mechanical stress generated during the processing is evenly distributed in the composite tube, which is conducive to better coordinated deformation between Cu and Fe in the MgB2 single core rod during multiple cold processing, improve the deformation uniformity of the core wire of the MgB2 superconducting wire, and enhance the current carrying performance of the wire.
[0008] 2. After the high-purity Mg powder is pressed into a rod, a layer of MgAl (magnesium-aluminum) alloy foil is wrapped on the outside. The MgAl alloy has a certain strength and acts as an interface to isolate the powder rod and the B powder to prevent mutual diffusion between the two during processing. The powder rod is different from the metal Mg rod and can avoid problems such as breakage and necking. More importantly, the Al element in the alloy foil is very close to Mg in electronic structure. It can be used as a doping element to replace Mg in the MgB2 lattice during the phase heat treatment process, causing lattice distortion, thereby increasing the critical current density of MgB2. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0010] Figure 1 Schematic diagram of the Fe tube and Cu coating in the CuFe composite tube provided in an embodiment of the present application.
[0011] Figure 2 This is a schematic diagram of the structure of the MgB2 single core rod provided in an embodiment of the present application.
[0012] Description of the accompanying drawings: 1. Fe tube; 2. Cu coating; 3. CuFe composite tube; 4. B powder; 5. MgAl alloy foil; 6. Mg powder rod. DETAILED DESCRIPTION
[0013] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0014] The present invention provides a method for preparing a MgB2 superconducting wire, which comprises the following steps: S100, a Cu coating 2 is attached to the outer surface of the Fe tube 1 by electroplating to obtain a CuFe composite tube 3, such as Figure 1 shown.
[0015] For example, before electroplating, the Fe tube 1 is first cleaned, and then both ends of the cleaned Fe tube 1 are sealed with corrosion-resistant rubber sleeves before electroplating. Specifically, the cleaning of the Fe tube 1 includes degreasing, washing and drying, wherein a metal degreasing agent is used for degreasing, and hydrochloric acid is used for washing.
[0016] Furthermore, the purity of the Fe tube 1 is 99.9%, the outer diameter is 10 mm to 30 mm, the wall thickness is 1 to 3 mm, and the length is 800 to 1500 mm. The Fe tube 1 is cleaned with 15% to 20% hydrochloric acid, and the length of the corrosion-resistant rubber sleeve inserted into the Fe tube 1 does not exceed 5 mm.
[0017] During electroplating, copper is used as an anode, and the Fe tube 1 with both ends sealed is used as a cathode. A copper sulfate electrolyte is added to the electrolytic cell, and the temperature and current density are controlled to electroplate a Cu plating layer 2 of uniform thickness on the outer surface of the Fe tube 1. Specifically, during the electroplating process, the temperature and current density of the electrolytic cell are controlled according to the required Cu / Fe ratio, so that a Cu plating layer 2 of a required thickness is deposited on the Fe tube 1.
[0018] Furthermore, the anode used for electroplating is a copper plate or copper rod with a purity greater than 99%, and the thickness of the Cu plating layer 2 is 0.3-2 mm.
[0019] After the electroplating is completed, the corrosion-resistant rubber sleeve is removed, and the unplated parts at both ends of the Fe tube 1 are sawed off and cut to a fixed length to obtain the CuFe composite tube 3.
[0020] Furthermore, the cut-to-length of the CuFe composite tube 3 is 800-1000 mm.
[0021] After the CuFe composite tube 3 is obtained by electroplating, the CuFe composite tube 3 is cleaned and dried.
[0022] S110, pressing the Mg powder into a Mg powder rod 6.
[0023] For example, the Mg powder used in the pressed rod has an average particle size of 50 μm and a purity of 99.9%. The pressed Mg powder rod 6 has an outer diameter of 6 to 15 mm and a length of 800 to 1000 mm.
[0024] S120 , wrapping the outer surface of the Mg powder rod 6 with the MgAl alloy foil 5 , and inserting the Mg powder rod 6 wrapped with the MgAl alloy foil 5 into the CuFe composite tube 3 .
[0025] Exemplarily, the Al content in the used MgAl alloy foil 5 is less than 3%, the total content of trace elements does not exceed 0.1%, and the rest is Mg. The MgAl alloy foil 5 is 800~1200mm long and 0.1~1mm thick. The MgAl alloy foil 5 is rolled into a cylindrical tube and tightly wrapped around the outside of the Mg powder rod 6.
[0026] S130, filling B powder 4 between the Mg powder rod 6 and the CuFe composite tube 3, sealing both ends of the CuFe composite tube 3, and obtaining a MgB2 single core rod, such as Figure 2 shown.
[0027] For example, when filling the B powder 4, first weigh an appropriate amount of the B powder 4 according to the set mass ratio of Mg to B, and then fill the B powder 4 in the CuFe composite tube 3. The B powder 4 is an amorphous B powder with an average particle size of 200 nm and a purity of 99.9%.
[0028] Before inserting the Mg powder rod 6 wrapped with the MgAl alloy foil 5 into the CuFe composite tube 3, a plug made of oxygen-free copper is first welded to one end of the CuFe composite tube 3, and then the Mg powder rod 6 is installed in the center of the plug, and then filled with B powder 4, and finally a plug is also welded to the other end of the CuFe composite tube 3.
[0029] The two plugs are provided with grooves on the surfaces facing the inside of the CuFe composite tube 3 . The grooves are located at the center of the bottom surface of the CuFe composite tube 3 . The two ends of the Mg powder rod 6 are respectively inserted into the two grooves.
[0030] S140, performing multiple rolling and cold drawing on the MgB2 single core rod to obtain a MgB2 single core wire.
[0031] For example, the processing amount of each pass in the rolling process is 15% to 20%, the processing amount of each pass in the cold drawing process is 10% to 15%, and the final wire diameter of the MgB2 single core wire is Ф0.5 to 1.0 mm.
[0032] S150, performing phase heat treatment on the MgB2 single core wire to obtain a MgB2 superconducting wire.
[0033] Exemplarily, the phase forming heat treatment is performed in a vacuum furnace, and the temperature of the phase forming heat treatment is 600° C. to 750° C., and the holding time is 2 h to 6 h.
[0034] The embodiment of the present application also provides a MgB2 superconducting wire, which is prepared by the above method.
[0035] Example 1 This embodiment includes the following steps: Step 1: First, use a metal degreasing agent to degrease the inner and outer surfaces of a Fe tube 1 with an outer diameter of 15mm, an inner diameter of 12mm, a length of 1100mm, and a purity of 99.9%, and then clean it with 20% hydrochloric acid to control the corrosion amount to no more than 50μm. When the inner and outer walls of the Fe tube 1 are bright and free of pits and scratches, take it out and seal the port of the Fe tube 1 with a corrosion-resistant rubber sleeve with a length of 5mm.
[0036] Step 2: A copper plate with a purity of 99% and a length, width and thickness of 1000×500×20 mm is used as a soluble anode, and the Fe tube 1 with a closed port obtained in step 1 is used as the cathode of the electrolytic cell. A Cu coating 2 with a thickness of 2 mm is uniformly plated on the surface of the Fe tube 1 by controlling the current density in a copper sulfate electrolyte.
[0037] Step 3: After removing the rubber sleeve portion of the Fe tube 1 with the 2 mm Cu coating 2 obtained in step 2, the tube is cut into a fixed length of 1000 mm to obtain a CuFe composite tube 3 with a Cu / Fe cross-sectional area ratio of 1.679.
[0038] Step 4: Clean and dry the CuFe composite tube 3 obtained in step 3 according to the cleaning process of Fe tube 1. Weigh 47g of Mg powder with an average particle size of 60μm and a purity of 99.9% according to the molar ratio of Mg:B=1.05:2, press it into a Mg powder rod 6 with an outer diameter of 6mm and a length of 1000mm, then take a MgAl alloy foil 5 with a thickness of 0.5mm and wrap it tightly on its outer surface to ensure that the outer surface is smooth and flat as a whole after coating, and then insert it into the center of the CuFe composite tube 3 closed at one end with a plug and fix it with a tooling so that it does not eccentric. Take about 55g of B powder 4 with an average particle size of 200nm and a purity of 99.9%, evenly fill the B powder 4 into the gap of the CuFe composite tube 3 and compact it with a mold. After being filled with powder, the port of the CuFe composite tube 3 is sealed with an oxygen-free copper plug of Φ11.90×15 mm to obtain a MgB2 single core rod with an outer diameter of Φ19 mm and a length of 1000 mm.
[0039] Step 5: The MgB2 single core rod obtained in step 4 is rolled from Ф19mm to Ф1.6mm by a cold rolling mill, and the processing amount of the rolling process is 18%. When the wire diameter is less than Ф1.6mm, a multi-mode wire drawing machine is used to process it into a final specification of MgB2 single core wire of Ф0.5mm, and the processing amount of the cold drawing process is 10%.
[0040] Step 6: Wind the MgB2 single-core wire in step 5 onto a steel wire wheel, put it into a vacuum furnace and keep it at 600°C for 6 hours. After high-temperature phase formation, a single-core MgB2 superconducting wire is finally obtained. Samples of the wire under this specification are taken for current-carrying performance testing, and its critical current density Jc=4010A / mm at 4.2K and 3T is measured. 2 .
[0041] Example 2 This embodiment includes the following steps: Step 1: First, use a metal degreasing agent to degrease the inner and outer surfaces of a Fe tube 1 with an outer diameter of 30mm, an inner diameter of 24mm, a length of 1100mm, and a purity of 99.9%, and then clean it with 20% hydrochloric acid to control the corrosion amount to no more than 50μm. When the inner and outer walls of the Fe tube 1 are bright and free of pits and scratches, take it out and seal the port of the Fe tube 1 with a corrosion-resistant rubber sleeve with a length of 5mm.
[0042] Step 2: A copper plate with a purity of 99% and a length, width and thickness of 1000×500×20 mm is used as a soluble anode, and the Fe tube 1 with a closed port obtained in step 1 is used as a cathode. A Cu coating 2 with a thickness of 2 mm is uniformly plated on the surface of the Fe tube 1 by controlling the current density in a copper sulfate electrolyte.
[0043] Step 3: After removing the rubber sleeve portion of the Fe tube 1 with the 2 mm Cu coating 2 obtained in step 2, the tube is cut into 1000 mm lengths to obtain a CuFe composite tube 3 with a Cu / Fe cross-sectional area ratio of 0.79.
[0044] Step 4: Clean and dry the CuFe composite tube 3 obtained in step 3 according to the cleaning process of Fe tube 1. Weigh 189g of Mg powder with an average particle size of 60μm and a purity of 99.9% according to the molar ratio of Mg:B=1.05:2, and press it into a Mg powder rod 6 with an outer diameter of 11mm and a length of 1000mm. Then take a MgAl alloy foil 5 with a thickness of 0.5mm and wrap it tightly against its outer surface to ensure that the outer surface is smooth and flat as a whole after coating, and then insert it into the center of the CuFe composite tube 3 with one end closed with a plug and fix it with a tooling so that it does not eccentric. Take about 218g of B powder 4 with an average particle size of 200nm and a purity of 99.9%, evenly fill the B powder 4 into the gap of the CuFe composite tube 3 and compact it with a mold. After being filled with powder, the three ports of the CuFe composite tube were sealed with oxygen-free copper plugs of Ф23.90×15mm to obtain a MgB2 single core rod with an outer diameter of Ф34mm and a length of 1000mm.
[0045] Step 5: The MgB2 single core rod obtained in step 4 is rolled from Ф34mm to Ф1.6mm by a cold rolling mill, and the processing amount during the rolling process is 18%. When the wire diameter is less than Ф1.6mm, a multi-mode wire drawing machine is used to process it into a final specification of MgB2 single core wire of Ф0.5mm, and the processing amount during the cold drawing process is 10%.
[0046] Step 6: Wind the MgB2 single-core wire in step 5 onto a steel wire wheel, put it into a vacuum furnace and keep it at 600°C for 6 hours. After phase formation, a single-core MgB2 superconducting wire is finally obtained. Samples of the wire under this specification are taken for current carrying performance testing, and its critical current density Jc=3986A / mm at 4.2K and 3T is measured. 2 .
[0047] Example 3 This embodiment includes the following steps: Step 1: First, use a metal degreasing agent to degrease the inner and outer surfaces of a Fe tube 1 with an outer diameter of 15mm, an inner diameter of 12mm, a length of 1100mm, and a purity of 99.9%, and then clean it with 20% hydrochloric acid to control the corrosion amount not to exceed 50μm. When the inner and outer walls of the Fe tube 1 are bright and free of pits and scratches, take it out and seal the port of the Fe tube 1 with a corrosion-resistant rubber sleeve with a length of 5mm.
[0048] Step 2: A copper plate with a purity of 99% and a length, width and thickness of 1000×500×20 mm is used as a soluble anode, and the Fe tube 1 with a closed port obtained in step 1 is used as the cathode of the electrolytic cell. A Cu coating 2 with a thickness of 1 mm is uniformly plated on the surface of the Fe tube 1 by controlling the current density in a copper sulfate electrolyte.
[0049] Step 3: After removing the rubber sleeve portion of the Fe tube 1 with the 2 mm Cu coating 2 obtained in step 2, the tube is cut into 1000 mm lengths to obtain a CuFe composite tube 3 with a Cu / Fe cross-sectional area ratio of 0.79.
[0050] Step 4: Clean and dry the CuFe composite tube 3 obtained in step 3 according to the cleaning process of Fe tube 1. Weigh 47g of Mg powder with an average particle size of 60μm and a purity of 99.9% according to the molar ratio of Mg:B=1.05:2, and press it into a Mg powder rod 6 with an outer diameter of 6mm and a length of 1000mm. Then take a MgAl alloy foil 5 with a thickness of 0.5mm and wrap it tightly against its outer surface to ensure that the outer surface is smooth and flat as a whole after coating, and then insert it into the center of the CuFe composite tube 3 with one end closed with a plug and fix it with a tooling so that it does not eccentric. Take about 55g of B powder 4 with an average particle size of 200nm and a purity of 99.9%, evenly fill the B powder 4 into the gap of the CuFe composite tube 3 and compact it with a mold. After being filled with powder, the port of the CuFe composite tube 3 is sealed with an oxygen-free copper plug of Φ11.90×15 mm to obtain a MgB2 single core rod with an outer diameter of Φ17 mm and a length of 1000 mm.
[0051] Step 5: The MgB2 single core rod obtained in step 4 is rolled from 17 mm to 1.6 mm using a cold rolling mill, and the processing amount during the rolling process is 18%. When the wire diameter is less than 2.5 mm, a multi-mode wire drawing machine is used to process it into a single core wire with a final specification of 0.5 mm, and the processing amount during the cold drawing process is 10%.
[0052] Step 6: Wind the MgB2 single-core wire in step 5 onto a steel wire wheel, put it into a vacuum furnace and keep it at 600°C for 6 hours. After phase formation, a single-core MgB2 superconducting wire is finally obtained. Samples of the wire under this specification are taken for current carrying performance testing, and its critical current density Jc=3999A / mm at 4.2K and 3T is measured. 2 .
[0053] Comparative Example 1 This comparative example comprises the following steps: Step 1: First, use a metal degreasing agent to degrease the inner and outer surfaces of a Fe tube with an outer diameter of 15mm, an inner diameter of 12mm, a length of 1100mm, and a purity of 99.9%, and then clean it with 20% hydrochloric acid to control the corrosion amount to no more than 50μm. When the inner and outer walls of the Fe tube are bright and free of pits and scratches, take it out and seal the Fe tube port with a corrosion-resistant rubber sleeve with a length of 5mm.
[0054] Step 2: A copper plate with a purity of 99% and a length, width and thickness of 1000×500×20 mm is used as a soluble anode, and the Fe tube with a closed end obtained in step 1 is used as the cathode of the electrolytic cell. A Cu coating with a thickness of 2 mm is uniformly plated on the surface of the Fe tube by controlling the current density in a copper sulfate electrolyte.
[0055] Step 3: After removing the rubber sleeve portion of the Fe tube with a 2 mm Cu coating obtained in step 2, the tube is cut into 1000 mm lengths to obtain a CuFe composite tube with a Cu / Fe cross-sectional area ratio of 1.679.
[0056] Step 4: Clean and dry the CuFe composite tube obtained in step 3 according to the cleaning process of the Fe tube. Weigh 47g of Mg powder with an average particle size of 60μm and a purity of 99.9% according to the molar ratio of Mg:B=1.05:2, and press it into a Mg powder rod with an outer diameter of 6mm and a length of 1000mm. Then take a piece of Mg foil with a thickness of 0.5mm and a purity of 99.9% and wrap it tightly on its outer surface to ensure that the outer surface is smooth and flat as a whole after coating, and then insert it into the center of the CuFe composite tube closed with a plug at one end and fix it with a tooling so that it does not eccentric. Take 55g of B powder with an average particle size of 200nm and a purity of 99.9%, evenly fill the B powder into the gap of the CuFe composite tube and compact it with a mold. After filling the powder, use a Ф11.90×15mm oxygen-free copper plug to seal the port of the CuFe composite tube to obtain a MgB2 single core rod with an outer diameter of Ф19mm and a length of 1000mm.
[0057] Step 5: The MgB2 single core rod obtained in step 4 is rolled from Ф19mm to Ф1.6mm by a cold rolling mill, and the processing amount of the rolling process is 18%. When the wire diameter is less than Ф1.6mm, a multi-mode wire drawing machine is used to process it into a final specification of MgB2 single core wire of Ф0.5mm, and the processing amount of the cold drawing process is 10%.
[0058] Step 6: Wind the MgB2 single-core wire in step 5 onto a steel wire wheel, put it into a vacuum furnace and keep it at 600°C for 6 hours. After phase formation, a single-core MgB2 superconducting wire is finally obtained. The wire of this specification is sampled for current carrying performance test, and its critical current density Jc=3500A / mm at 4.2K and 3T is measured. 2 .
[0059] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the present application.
[0060] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A method for preparing a MgB2 superconducting wire, characterized in that: include: A Cu coating (2) is attached to the outer surface of the Fe tube (1) by electroplating to obtain a CuFe composite tube (3); Pressing the Mg powder into a Mg powder rod (6); Wrapping an MgAl alloy foil (5) on the outer surface of the Mg powder rod (6), and inserting the Mg powder rod (6) wrapped with the MgAl alloy foil (5) into the CuFe composite tube (3); Filling B powder (4) between the Mg powder rod (6) and the CuFe composite tube (3), sealing both ends of the CuFe composite tube (3), and obtaining a MgB2 single core rod; The MgB2 single core rod is subjected to multiple rolling and cold drawing to obtain a MgB2 single core wire; The MgB2 single core wire is subjected to phase heat treatment to obtain a MgB2 superconducting wire.
2. The method for preparing a MgB2 superconducting wire according to claim 1, characterized in that: Before electroplating, the Fe tube (1) is first cleaned, and then both ends of the cleaned Fe tube (1) are sealed with corrosion-resistant rubber sleeves, and then electroplating is performed.
3. The method for preparing a MgB2 superconducting wire according to claim 1, characterized in that: The cleaning of the Fe tube (1) includes degreasing, washing and drying. A metal degreasing agent is used for degreasing and hydrochloric acid is used for washing.
4. The method for preparing a MgB2 superconducting wire according to claim 2, characterized in that: During electroplating, copper is used as an anode, the Fe tube (1) with both ends sealed is used as a cathode, copper sulfate electrolyte is added to the electrolytic cell, the temperature and current density are controlled, and a Cu plating layer (2) with a uniform thickness is electroplated on the outer surface of the Fe tube (1).
5. The method for preparing a MgB2 superconducting wire according to claim 2, characterized in that: After the electroplating is completed, the corrosion-resistant rubber sleeve is removed, and the unplated portions at both ends of the Fe tube (1) are sawed off to obtain the CuFe composite tube (3).
6. The method for preparing a MgB2 superconducting wire according to claim 2, characterized in that: After the CuFe composite tube (3) is obtained by electroplating, the CuFe composite tube (3) is cleaned and dried.
7. The method for preparing a MgB2 superconducting wire according to claim 1, characterized in that: Before the Mg powder rod (6) wrapped with the MgAl alloy foil (5) is inserted into the CuFe composite tube (3), a plug is first welded to one end of the CuFe composite tube (3), then the Mg powder rod (6) is installed in the center of the plug, then the B powder (4) is filled, and finally the plug is also welded to the other end of the CuFe composite tube (3).
8. The method for preparing a MgB2 superconducting wire according to claim 7, characterized in that: The two plugs are provided with grooves on the surface facing the inside of the CuFe composite tube (3), the grooves being located at the center of the bottom surface of the CuFe composite tube (3), and the two ends of the Mg powder rod (6) are respectively inserted into the two grooves.
9. A MgB2 superconducting wire, characterized in that: The MgB2 superconducting wire is prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method of preparing MgB2 superconducting material
CN101058508A
High performance Fe / Cu wrapping structure magnesium diboride multiple core superconductive wire preparation method
CN101150004A
Preparation method for multi-core MgB2 / Fe / Cu superconducting wire
CN102693785A
High-temperature structure and function integrated Mg(Al)B2 and B4C co-enhanced aluminum-based neutron absorbing material and preparation method thereof
CN111349805A
TiNb alloy electrode and preparation method and application thereof
CN115846661A